From camera traps to conservation: biodiversity and mammal functional diversity in the Langkloof Corridor, Eastern Cape province, South Africa - Van Graan, Erik De Kock (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScConEcol)--Stellenbosch University, 2025.